Twentieth-century paleoclimatic modeling of borehole temperatures in western and central Anatolia regions, Turkey - ERKAN, KAMİL; TAYANÇ, METE (SPRINGER, 2019)
Understanding the change in the climate at the regional scale during the industrial period is essential for future climate projections. Among various proxy methods, temperatures from thermally conductive boreholes offer a direct method of determination of surface temperatures changes in time. In this study, we use temperature-depth data from six boreholes in western and central Anatolia regions of Turkey, and present reconstructions of the surface temperatures during the last century. The boreholes are located in rural areas where urban heat island effects are minimal. Regionally averaged GST models give cooling of 0.33 degrees C and 0.42 degrees C between 1900 and 1990, and warming of 1.47 degrees C and 1.66 degrees C between 1990 and 2010, for the western and central Anatolian sites, respectively. The overall changes in the surface temperatures since the beginning of the twentieth-century are calculated to be +1.14 degrees C and +1.13 degrees C, in each region. The instrumental SAT records in these regions which are available from 1950 show a general agreement with the GST models. The rate of recent warming since the early 1990's is calculated to be 5.7 degrees C per 100-year for both regions. This value is within the range proposed by regional climate projections for the Eastern Mediterranean region.
Keywords: Paleoclimate; Climate; Borehole; Anatolia; Turkey; CLIMATE-CHANGE; AIR-TEMPERATURE; RECONSTRUCTION; HISTORY; TRENDS; RECORD; PROXY